Efficacy and safety of "unboosting" atazanavir in a randomized controlled trial among HIV-infected patients receiving tenofovir DF. Issue 1 (2nd January 2017) - Harris, Marianne; Ganase, Bruce; Watson, Birgit; Hull, Mark W.; Guillemi, Silvia A.; Zhang, Wendy; Saeedi, Ramesh; Harrigan, P. Richard
Abstract : Objectives: To assess safety and efficacy of a switch to unboosted atazanavir (ATV) among HIV-infected adults receiving ATV/ritonavir (r) and tenofovir disoproxil fumarate (TDF). Methods: HIV-infected adults with viral load (VL) <40 copies/mL at screening and <150 copies/mL consistently for ≥3 months while receiving a regimen including ATV/r and TDF were randomized to continue ATV/r 300/100 mg daily (control) or change to ATV 400 mg daily (switch), while maintaining their TDF backbone. The primary outcome was proportion of subjects without treatment failure (regimen switch or VL > 200 copies/mL twice consecutively) at 48 weeks. Results : Fifty participants (46 male, median age 47 years) were randomized, 25 to each arm. At week 48, treatment success occurred in 76% in the control arm and 92% in the switch arm (ITT, p = 0.25). ATV trough levels at week 9 were higher in controls (median 438 ng/mL) than in the switch arm (median 124 ng/mL) ( p = 0.003), as was total bilirubin at week 48 (median 38 μmol/L and 28 μmol/L, respectively; p = 0.02). Estimated glomerular filtration rate (eGFR) decreased in the control arm ( p = 0.007), but did not change in the switch arm. At week 48, eGFR was higher in the switch arm (median 96 mL/min) than in the control arm (median 85 mL/min) ( p = 0.035), but the arms were similar with respect to fasting glucose, C-reactive protein, and lipid parameters. Conclusions: Switching from ATV/r to unboosted ATV appears to be safe and effective in selected virologically suppressed patients receiving TDF-containing regimens, and may have favorable effects on bilirubin and renal function.